2015
DOI: 10.1074/jbc.m115.671164
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis RecG Protein but Not RuvAB or RecA Protein Is Efficient at Remodeling the Stalled Replication Forks

Abstract: Background: Helicases are implicated in fork remodeling. Results: Mycobacterium tuberculosis RecG helicase/translocase remodels stalled replication forks. Conclusion: M. tuberculosis RecG but not RuvAB or RecA is efficient in fork reversal activity. Significance: This study identifies a fork remodeling enzyme and provides insights into fork restart mechanisms in M. tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…Similarly, RecG is a structure‐specific helicase that binds and unwinds branched DNA structures that are intermediates of DNA repair/recombination/replication . Previously we showed that M. tuberculosis RecG (MtRecG) efficiently remodels the stalled replication forks . To test whether MtRecG can also resolve G4 DNA structures in vitro , we incubated increasing concentrations of MtRecG with TPB‐G4‐3′T15 (15‐nt 3′‐overhang) structures.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, RecG is a structure‐specific helicase that binds and unwinds branched DNA structures that are intermediates of DNA repair/recombination/replication . Previously we showed that M. tuberculosis RecG (MtRecG) efficiently remodels the stalled replication forks . To test whether MtRecG can also resolve G4 DNA structures in vitro , we incubated increasing concentrations of MtRecG with TPB‐G4‐3′T15 (15‐nt 3′‐overhang) structures.…”
Section: Resultsmentioning
confidence: 99%
“…Purified RecG protein has 3′–5′ helicase and nucleic acid translocase activities. In vitro , it can bind and unwind synthetic model Holliday junctions and various other types of branched DNA substrates including replication forks, D‐loops and R‐loops . Unlike most other helicases, this enzyme unwinds DNA by translocating on dsDNA rather than on ssDNA.…”
Section: Recg Protein Unwinds and Remodels Branched Dna Molecules In mentioning
confidence: 99%
“…This RecG‐catalysed replication fork reversal reaction has been observed using an oligonucleotide substrate with nascent strands annealed to both the leading‐ and lagging‐strand templates , a replication fork in supercoiled plasmid DNA and a replication fork blocked at a DNA lesion in an in vitro replication system where the DNA polymerase and the replicative helicase remain associated with the DNA . These studies have led to the opinion that replication fork reversal is an important biochemical activity of RecG . RecG can catalyse this reaction thanks to its unusual structure .…”
Section: Recg Protein Unwinds and Remodels Branched Dna Molecules In mentioning
confidence: 99%
“…But what might drive fork reversal and how might replication resume? A possible scenario emerged when E. coli RecG protein was shown to catalyse the interconversion of fork and Holliday junction structures in vitro (McGlynn and Lloyd 2000 ), a result recapitulated with RecG proteins from other bacteria (Zegeye et al 2012 ; Thakur et al 2015 ). Indeed, recent in vitro studies exploiting substrates and conditions that more closely mimic the situation likely to be encountered at a stalled fork in vivo confirmed that RecG is able to drive fork reversal and revealed that dissociation of the replisome is probably not a pre-requisite (Gupta et al 2014 ).…”
Section: Re-starting Replication At Stalled or Damaged Forksmentioning
confidence: 99%